Profil Kemampuan Berpikir Kritis Mahasiswa Program Studi Pendidikan IPA dalam Kasus Grafik Kinematika Satu Dimensi - Intan Ekananda Kirana; Sentot Kusairi (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study aims to examine students' critical thinking skills on a one-dimensional kinematics graph. This quantitative descriptive model involved 51 final semester students and 32 early semester students. The test instrument was in the form of two description questions with 4 indicators of critical thinking skills, namely interpretation, analysis, evaluation, and inference. The results show that students have critical thinking skills in the low category, with the average score of the final semester students being slightly higher than the average grade of the early semester students. Students have difficulty determining the instantaneous speed of the graph of the time and displacement position of the time velocity graph.Abstrak: Penelitian ini bertujuan menguji kemampuan berpikir kritis mahasiswa pada grafik kinematika satu dimensi. Model deskriptif kuantitatif ini melibatkan 51 mahasiswa semester akhir dan 32 mahasiswa semester awal. Instrumen tes berupa dua soal uraian dengan empat indikator kemampuan berpikir kritis, yaitu interpretasi, analisis, evaluasi, dan inferensi. Hasil menunjukkan bahwa mahasiswa memiliki kemampuan berpikir kritis pada kategori rendah, dengan nilai rata-rata mahasiswa semester akhir sedikit lebih tinggi dari pada nilai rata-rata mahasiswa semester awal. Mahasiswa kesulitan menentukan kecepatan sesaat dari grafik posisi waktu dan perpindahan dari grafik kecepatan waktu.